Orthognathic surgery in a patient with von Willebrand disease: case report - Barcellos, Bhárbara Mariano (2024)
Aim: This study aims to report the perioperative management of a patient with von Willebrand disease (vWd) who underwent orthognathic surgery. The report follows the guidelines of the Case Report Guidelines (CARE) and focuses on the steps taken to prevent bleeding during the surgical procedure. Methods: A 39-year-old female patient with skeletal Class III was treated with maxillary advancement and mandibular setback. Despite normal test results for ristocetin cofactor activity, measures were taken to prevent bleeding, including atraumatic surgical techniques, use of antifibrinolytic medication, induced hypotension during anesthesia, and preparation of blood products for transfusion during trans and postoperative periods if needed. In the end, these measures were not required. Results: The patient did not experience any bleeding during the surgical procedure or postoperative period, demonstrating the effectiveness of the measures taken to manage their blood dyscrasia. Two years after the surgery, the patient had satisfactory aesthetic and functional results and no evidence of relapse. Conclusion: Thus, this case report demonstrates that vWd does not prevent largescale oral and maxillofacial surgeries such as orthognathic surgery as long as proper precautions are taken pre-, intraand postoperatively.